2015
DOI: 10.1039/c5ra04589d
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the microbial degradation of polyurethanes

Abstract: Frequent and frequently deliberate release of plastics leads to accumulation of plastic waste in the environment which is an ever increasing ecological threat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 114 publications
(140 reference statements)
1
81
0
2
Order By: Relevance
“…In experiments performed under similar conditions, Impranil degradation by the endophytic fungus Pestalotiopsis microspora was observed as a decrease in the carbonyl signal (CAO) and, although not mentioned by the authors, the spectrum also showed decreases in the signals at 1,540 and 1,260 cm Ϫ1 , which, as in our work, implies enzymatic attack on the urethane group (15). Attack on these functional groups, ester and urethane, has been suggested to be performed by bacterial hydrolytic enzymes, such as esterase, protease, and urease (4,8). In our work, evidence of the activity of fungal enzymes on Impranil biodegradation was also detected by GC-MS analysis after the incubation of Impranil with the best PU-degrading fungus C. pseudocladosporioides T1.PL.1, an approach not explored in any other previous work, to our knowledge.…”
Section: Discussionmentioning
confidence: 55%
“…In experiments performed under similar conditions, Impranil degradation by the endophytic fungus Pestalotiopsis microspora was observed as a decrease in the carbonyl signal (CAO) and, although not mentioned by the authors, the spectrum also showed decreases in the signals at 1,540 and 1,260 cm Ϫ1 , which, as in our work, implies enzymatic attack on the urethane group (15). Attack on these functional groups, ester and urethane, has been suggested to be performed by bacterial hydrolytic enzymes, such as esterase, protease, and urease (4,8). In our work, evidence of the activity of fungal enzymes on Impranil biodegradation was also detected by GC-MS analysis after the incubation of Impranil with the best PU-degrading fungus C. pseudocladosporioides T1.PL.1, an approach not explored in any other previous work, to our knowledge.…”
Section: Discussionmentioning
confidence: 55%
“…Because neither urethane nor amines or ammonium were detected by GC‐MS in the supernatants of the culture media, it is likely that these groups were consumed by the bacteria as soon as they were generated. Evidences supporting the action of esterase activities on PS‐PU biodegradation have been reported previously . As far as we know, evidence for the action of an amidase activity hydrolyzing the urethane group in a polymeric material has not been reported yet.…”
Section: Resultsmentioning
confidence: 75%
“…Poly(urethane)s elastomer has constituted one of the most versatile classes of polymeric materials because of remarkable properties including flexibility, rigidness, thermal stability, diverse utility, and relatively low‐cost production. Thus, polyurethanes have been used in a broad range of applications including foams, coatings, adhesives, elastomers, furniture, sealants, synthetic leathers, membranes, and heat insulators to the biomedical products . Generally, poly(urethane) elastomer was synthesized using the polyaddition of diol (HOROH) and diisocyanates (NCOR′NCO) derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, polyurethanes have been used in a broad range of applications including foams, 1,2 coatings, 1,2 adhesives, 1,2 elastomers, 1,2 furniture, 2 sealants, 1 synthetic leathers, 2 membranes, 1,3 and heat insulators to the biomedical products. 1,3 Generally, poly(urethane) elastomer was synthesized using the polyaddition of diol (HO R OH) and diisocyanates (NCO R 0 NCO) derivatives. The selection of monomer structure is important to achieve the desired property of poly(urethane).…”
mentioning
confidence: 99%